Pasture seed production in Colombia - Ferguson, John E. (International Center for Tropical Agriculture, 1980)
Within Colombia significant amounts of seed are produced and exported of the perennial tropical grasses; Brachiaria decumbens, Cenchus ciliaris, Dichanthium aristatum, Hyparrhenia rufa, Melinis minutiflora, and Panicum maximum. Small amounts of the perennial legume Pueraria phaseoloides are produced. There are very few seed producers in Colombia in the conventional sense. This apparent anomaly is explained by the fact that seed is natural by-product in some grazing regions which is harvested from pastures by manual contract labour and then traded between merchants, generally without any mechanical processing. While at present production of seed is a secondary, opportunistic, low technology, highly manual enterprise, the seed industry is changing rapidly. In recent years, a few specialist producers and processors have had dramatic effects in improving species range, production and seed quality. Future prospects appear to be favourable.